The Characteristics of the Open Innovation Model Application in Slovenian Firms - Daša Farčnik; Tjaša Redek (Dynamic Relationships Management Journal (DRMJ), 2015)
This paper analyses the characteristics of the model of open innovation in Slovenia. On the basis of activities that are defined by the model of open innovation (Chesbrough, 2003) 222 companies are divided into three groups : companies that do not apply open innovation activities, companies with limited scope of activities of open innovation and companies engaged in the majority of open innovation activities. Three groups of firms also differ with regard to the organizational structure, attitude of staff and management towards the open innovation activities, expenditures for research and development and success of the introduction of new products, process innovation and success of these products and services on the market. Analysis combines the dominant model of innovation model with the open innovation model. Further on it is encouraging that all three groups do not differ regarding their future plans of introducing the model of open innovation activities.